Design of linear induction electron accelerator LIA-R - Gordeev, V.S.; Myskov, G.А.; Mikhailov, Е.С. (Вопросы атомной науки и техники, 2006)
A design of linear induction electron accelerator LIA-R meant for generation of bremsstrahlung pulse of duration
~ 50 ns at half maximum is presented. As well as a facility LIA-10M the accelerator consists of an injector and
16 standard acceleration modules. As an injector it is supposed to use a modification of STRAUS-R accelerator developed
on the basis of five-cascade double stepped forming line (DSFL) of diameter 1.2 m with water insulation.
Inductors will be made on the basis of four-cascade DSFL of diameter 1 m. It is expected to accelerate the electron
beam up to the energy ~30 MeV at the acceleration rate ~1 MeV/m. Представлен проект линейного индукционного ускорителя электронов ЛИУ-Р, предназначенного для генерации импульса тормозного излучения длительностью ∼ 50 нс. Как и установка ЛИУ-10М ускоритель состоит из инжектора и 16 типовых ускорительных модулей. В качестве инжектора предполагается использовать модификацию ускорителя СТРАУС-Р, разработанного на базе пятикаскадной двойной ступенчатой формирующей линии (ДСФЛ) диаметром 1.2 м с водяной изоляцией. Индукторы будут выполнены на базе четырехкаскадной ДСФЛ диаметром 1 м. Электронный пучок предполагается ускорять до энергии ∼30 МэВ при темпе ускорения ∼ 1 МэВ/м. Представлено проект лінійного індукційного прискорювача електронів ЛІП-Р, призначеного для
генерації імпульсу гальмового випромінювання тривалістю ∼ 50 нс. Як і установка ЛІП-10М прискорювач
складається з інжектора і 16 типових прискорювальних модулів. Як інжектор передбачається використати
модифікацію прискорювача СТРАУС-Р, розробленого на базі п’ятикаскадної подвійної східчастої
формуючої лінії (ПСФЛ) діаметром 1,2 м з водяною ізоляцією. Індуктори будуть виконані на базі
чотирьохкаскадної ПСФЛ діаметром 1 м. Електронний пучок передбачається прискорювати до енергії
30 МеВ при темпі прискорення 1 МеВ/м.